Constructing Knowledge and Technology Transfer Model for SMEs Technology Development in Emerging Economies - Fourry Handoko (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
Technology innovations occur in stages. The stages begin by discovering scientific knowledge generated from basic research. The findings of basic research are used to generate developments associated with its ‘applicability’, and are then developed and tested in accordance with knowledge, economically relevant procedures, and technically sound (development process) procedures. Moreover, in-depth knowledge investigation (learning process) will produce innovation of equipment, processes, and products. Innovations will undergo a process of adaptation (adaptation process) in order to meet technical standards, productivity, and social influence of technology application. This paper constructs a model of sustainable knowledge and technology. The proposed model identifies the key factors of knowledge and technology transfer. The model was constructed based on system-based model of inputs-transformations-outputs.